Lehr-Lern-Prozesse zum mathematischen Modellieren im Lehr-Labor MiℝA+ initiieren und erforschen (mathematica didactica, 2020)
In the context of the teaching laboratory MiℝA+, we focus on the professionalisation of prospective teachers through reflected practical experience. For this purpose, we take aspects of professional competence to teach mathematical modelling into account. In particular, the promotion of modelling-specific diagnostic and task competence is one of the focuses of the teaching laboratory seminar. This contribution provides insights into the concept of the teaching laboratory and reports the results of a quantitative study in which we are examining the development of these facets of participating students.